Electroosmotic dewatering of gelatinous materials: model development and analysis - Jami, Mohammed Saedi; Tanaka, Takanori; Fujihara, Kenji; Iwata, Masashi (2013)
Electroosmotic dewatering experiments under constant electric current density of superabsorbent hydrogel and bentonite suspended in aqueous media were carried out and comparison is made between the experimental results and model predictions. The basic differential equation based on the model is solved analytically by assuming that both an electro-osmotic pressure gradient Epg and a modified consolidation coefficient Ce of the material are constant. The solution can explain the time course of changes in a solid compressive pressure distribution. The electrode reaction may affect the dewatering of superabsorbent hydrogel．